2021
DOI: 10.1002/mame.202000730
|View full text |Cite
|
Sign up to set email alerts
|

Anisotropy Effects in the Shape‐Memory Performance of Polymer Foams

Abstract: Isotropic and anisotropic shape‐memory polymer foams are prepared by supercritical carbon dioxide foaming from a multiblock copolymer (PDLCL) consisting of poly(ω‐pentadecalactone) and poly(ε‐caprolactone) segments. Analysis by micro‐computed tomography reveals for the anisotropic PDLCL foam cells a high shape anisotropy ratio of R = 1.72 ± 0.62 with a corresponding Young's compression moduli ratio between longitudinal and transversal direction of 4.3. The experimental compression data in the linear elastic ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…16,17 Elements for the mercantile growth of foams contain lightness, inexpensiveness, lower thermal conductivity, a broad domain of formulations from hard foam to elastic foam, a number of different processes, simple production of various parts, absence of pressure in several production methods, the higher strength-to-mass ratio in analogy to another polymer families and great impact. [18][19][20][21] In extrusion foaming processes, due to the high pressure, the gas injected into the polymer melt dissolves. The dissolution of the gas causes the polymer melt to plasticize, resulting in a uniform polymer-gas mixture flowing along the extruder.…”
Section: Introductionmentioning
confidence: 99%
“…16,17 Elements for the mercantile growth of foams contain lightness, inexpensiveness, lower thermal conductivity, a broad domain of formulations from hard foam to elastic foam, a number of different processes, simple production of various parts, absence of pressure in several production methods, the higher strength-to-mass ratio in analogy to another polymer families and great impact. [18][19][20][21] In extrusion foaming processes, due to the high pressure, the gas injected into the polymer melt dissolves. The dissolution of the gas causes the polymer melt to plasticize, resulting in a uniform polymer-gas mixture flowing along the extruder.…”
Section: Introductionmentioning
confidence: 99%
“…The anisotropy of cells is important in designing anisotropic mechanical and thermal properties of foams. , Huber and Gibson reported that the anisotropy of mechanical properties such as the anisotropy ratio of Young’s modulus and plastic collapse could be significantly impacted by the shape of the cells . Martín-de León et al, who studied the effect of hot-bath and hot-press foaming methods, reported that hot-pressed foams show hardly any anisotropy .…”
Section: Resultsmentioning
confidence: 99%
“…16 In one study, the longitudinal (LD) compressive modulus became 4.3 times higher than the compressive modulus of the transversal direction (TD) for a foam with a shape anisotropy ratio of 1.72. 17 In addition, the anisotropic foam also demonstrated anisotropy in thermal conductivity. For example, freeze-dried aerogels and foams with tubular cellular structures exhibited thermal conductivity anisotropy and oil absorption capability.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation